2023
DOI: 10.21511/ppm.21(1).2023.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between human resource management practices, employee satisfaction, service quality, and employee service behavior in the hotel industry

Abstract: The hotel industry is critical in developing the economy. Moreover, it is the largest and most rapidly growing industry in Jordan. Employee satisfaction is a crucial element for the success of any organization, particularly in the hotel industry. Therefore, this study aims to examine the influence of human resource management (HRM) practices since these constructs could influence different outcomes at the workplace, such as employee satisfaction, service quality, and employee service behavior in the hotel indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The results show that each influences employee satisfaction. Likewise (Hussein et al, 2023) reveal that employees' positive perceptions about the human resource practice increase their satisfaction with their organisation. (Alsafadi & Altahat, 2021), Revealed that management practices positively and significantly impact employee satisfaction at the bank.…”
Section: Discussionmentioning
confidence: 98%
“…The results show that each influences employee satisfaction. Likewise (Hussein et al, 2023) reveal that employees' positive perceptions about the human resource practice increase their satisfaction with their organisation. (Alsafadi & Altahat, 2021), Revealed that management practices positively and significantly impact employee satisfaction at the bank.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that transformational leadership is connected to employee job satisfaction across different cultures and settings (Akdere & Egan, 2020; Gyensare et al, 2016;Musinguzi et al, 2018). Transformational leaders increase worker motivation as well as intrinsic satisfaction by communicating an inspiring vision, providing personal support, and linking work to higher purposes (Hoch et al, 2018;Hussein et al, 2023;Mohammad et al, 2023). Conversely, ongoing rewards in the form of transactional leadership fail to provide the motivation and reasons needed for high levels of satisfaction (Abbas, 2017;Mohammad et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…10.6 million people live in Jordan, a nation in the Eastern Mediterranean, which has an area of 89,342 square kilometres. [8][9][10]. Jordan shares borders with Saudi Arabia, Syria, the occupied Palestinian territories, and Iraq.…”
Section: Covid-19 and The Healthcare Management Performancementioning
confidence: 99%